A Calcium-Independent Activation of the Arabidopsis SOS2-Like Protein Kinase24 by Its Interacting SOS3-Like Calcium Binding Protein1. Issue 4 (12th February 2014) - Lin, Huixin; Du, Wenming; Yang, Yongqing; Schumaker, Karen S.; Guo, Yan
Abstract : Calcium-independent protein kinase activity is important for inactivating Arabidopsis plasma membrane proton-translocating adenosine triphosphatase . Abstract: The salt stress-induced SALT-OVERLY-SENSITIVE (SOS) pathway in Arabidopsis ( Arabidopsis thaliana ) involves the perception of a calcium signal by the SOS3 and SOS3-like CALCIUM-BINDING PROTEIN8 (SCaBP8) calcium sensors, which then interact with and activate the SOS2 protein kinase, forming a complex at the plasma membrane that activates the SOS1 Na + /H + exchanger. It has recently been reported that phosphorylation of SCaBP proteins by SOS2-like protein kinases (PKSs) stabilizes the interaction between the two proteins as part of a regulatory mechanism that was thought to be common to all SCaBP and PKS proteins. Here, we report the calcium-independent activation of PKS24 by SCaBP1 and show that activation is dependent on interaction of PKS24 with the C-terminal tail of SCaBP1. However, unlike what has been found for other PKS-SCaBP pairs, multiple amino acids in SCaBP1 are phosphorylated by PKS24, and this phosphorylation is dependent on the interaction of the proteins through the PKS24 FISL motif and on the efficient activation of PKS24 by the C-terminal tail of SCaBP1. In addition, we show that Thr-211 and Thr-212, which are not common phosphorylation sites in the conserved PFPF motif found in most SCaBP proteins, are important for this activation. Finally, we also found that SCaBP1-regulated PKS24 kinase activity is important for inactivating the Arabidopsis plasma membrane proton-translocating adenosine triphosphatase. Together, these results suggest the existence of a novel SCaBP-PKS regulatory mechanism in plants.